Bubble temperature measurements on seven binary mixtures containing 1-4-Dimethylbenzene at 95.8 kPa - Vittal Prasad T.E.; Prasad D.H.L.; Patanjali V. (My University, 2025)
Bubble temperatures at 95.8 kPa over the entire composition range are measured for the binary mixtures formed by 1,4-dimethylbenzene with heptane, hexane, cyclohexane, methylethylketone, tetrahydrofuran, trichlorethylene, and tetrachloroethylene. A Swietoslawski-type ebulliometer was used for the measurements. The composition versus temperature measurements are well represented by the Wilson model. Copyright © Taylor & Francis Inc.